2022
DOI: 10.1186/s40337-022-00616-8
|View full text |Cite
|
Sign up to set email alerts
|

Virtual prevention of eating disorders in children, adolescents, and emerging adults: a scoping review

Abstract: Background During the COVID-19 pandemic, there was a necessity for eating disorder (ED) outpatient treatment to be delivered virtually. Given this transition, and the surge in new ED cases, there was an urgent need to investigate virtually delivered ED prevention programs. This review aimed to identify the available evidence on virtual ED prevention programs for children, adolescents, and emerging adults. Method Using scoping review methodology, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 94 publications
(144 reference statements)
0
3
0
Order By: Relevance
“…AN incidence, including cases requiring hospitalisation, increased dramatically during the COVID-19 pandemic (Haripersad et al, 2021). Remote mental health interventions surged during the lockdown are continued in the post-pandemic period when health restrictions no longer apply (Pellegrini et al, 2022). There is considerable evidence to indicate that virtual mental health care is a promising therapeutic modality.…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…AN incidence, including cases requiring hospitalisation, increased dramatically during the COVID-19 pandemic (Haripersad et al, 2021). Remote mental health interventions surged during the lockdown are continued in the post-pandemic period when health restrictions no longer apply (Pellegrini et al, 2022). There is considerable evidence to indicate that virtual mental health care is a promising therapeutic modality.…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…They found that all respondents considered virtual treatment during confinement feasible and valuable. Pellegrini et al (2022) looked at the available evidence for virtual ED prevention programs for children, adolescents, and young adults and suggested that virtual workshops can effectively prevent EDs [34].…”
Section: Introductionmentioning
confidence: 99%
“…he phenomenon of an increasing overweight population is one of the most significant social, economic, and health challenges of the 21st century (Vizzuso et al, 2021). Among these, eating disorders are considered common mental/psychosomatic disorders that lead to numerous problems in physical health, psychological functioning, and the quality of life of adolescents (Pellegrini et al, 2022). Bulimia Nervosa is identified as a common eating disorder in adolescents (D'Souza et al, 2020), defined according to the current edition of the Diagnostic and Statistical Manual of Mental Disorders as episodes of binge eating and inappropriate compensatory behaviors occurring, on average, at least once a week for a minimum of three months (APA, 2022).…”
Section: Introductionmentioning
confidence: 99%